The position of cattle production in agricultural systems: A balance between food security and emission - de Jonge, L H (Food and Agricultural Sciences : Polije Proceedings Series, 2020)
The growth of the global population leads to an increase in demand for human edible food and cattle production plays an important role to realize this aim. Cattle or ruminants are capable to transfer fibre rich materials into human-edible products, such as meat and milk. This capability allows the exploitation of grassland, which is 50% of the land available for livestock, and the reuse of a large scale of by-products for the production of food. The use of non-human edible materials may make ruminants net producers of human-edible proteins. The disadvantages of this capability are the emission of methane, contribution to global warming, and the low milk N efficiency, leading to N emission to the environment contributing to water eutrophication, soil acidification, and global warming. Research work showed that the possibilities to reduce both types of emissions are relatively limited. The inclusion of more high-quality protein and starch into the diet reduces these emissions but this change also has a negative effect on the balance between the input of non-human edible material and the output of human-edible products. Balancing between both aspects is done by focusing on the ratio of emission units per animal product. This ratio should be minimized which can also be achieved by improvement of digestion of typical feed ingredients for ruminants, such as forage and fibre-rich by-products, leading to high animal production. Research work should focus on further improvement of the digestion of forages by technological, chemical, and biological treatments. The implementation of these improvements in practice, however, is a great challenge because it affects local agricultural systems and may lead to an increase in the price of animal products.